La proyección financiera y su impacto en la gestión económica y financiera del consorcio eléctrico de Villacuri SAC, año 2020 - Carbajal Azcárate, Jorge Carlos (2021)
This research work, raises the following problem: How does the financial projection impact on the Economic and Financial Management Del Consorcio Eléctrico De Villacuri SAC, Year 2020? being our main objective: How does the application of the financial projection affect the economic and financial management of the Consorcio Eléctrico De Villacuri, Year 2020. This research is classified as applied research due to the characteristics it presents, because once the problem is identified, the search for solutions begins, applying the knowledge acquired later such as: the analysis of the economic and financial situation, the horizontal and vertical analysis of the Financial Statements, application of the financial ratios, all these tools will serve as a base in the development of a financial planning according to the needs of the company; Thus corroborating the hypothesis raised, the financial projection positively affects the economic and financial management of the Consorcio Eléctrico De Villacuri SAC, Year 2020.